Urodynamic Testing After Spinal Cord Injury A Practical Guide - Wyndaele, Jean Jacques; Kovindha, Apichana; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book aims to provide a guide for urodynamic investigation in individuals who have suffered spinal cord injuries. It is universally acknowledged that this type of investigation is valuable and most international guidelines consider it mandatory in patients with neurogenic bladder dysfunction. The book offers an evidence based knowledge of applicability, clinical value, and limitation, and will give the reader strong diagnostic outcomes that will benefit patients suffering from spinal cord injuries. What is presented in this book is based on expert opinions acquired over decades of urodynamic testing that have taken place in different parts of the world.
1. Introduction -- 2. Physiology and pathophysiology -- 3. Indications and positioning in general diagnosis -- 4. Tests application -- 5. Rules for interpretation -- 6. Curves with data from clinical files, suggested interpretation, consequence for treatment.
Keywords: Medicine; Rehabilitation medicine; Traumatology; Urology; Medicine & Public Health; Traumatic Surgery; Rehabilitation medicine; Urology